Effect of cocoa (Theobroma cocoa) seed germination and seedling growth towards the treatment of synthetic amendment in sandy soil / Mohamad Nor Hazazy Mohamed - Mohamed, Mohamad Nor Hazazy (Faculty Of Plantation And Agrotechnology, 2018)
Increasing the number of population of human kind now a days can affect the resources used in thus world. Especially in the used of land and water resources used for domestic or other industries. Land and water efficiency is the basic material in agriculture sector, it is the importance factor in leading to achieved sustainability and increase the crop production of yield. By the larger share used of land and water in agriculture sector, the research and development department must create a new strategy to improve and optimise the land and water used efficiently is essential. Now, the used of coastal area or sandy soil area is less so by the improving the soil physical and chemical characteristic can utilize the used of this type of area. The usage one of synthetic amendment which is Superabsorbent polymer (SAPS) can be the strategies in this regard test with cocoa seed germination and growth. Briefly mentions from the previous studies that the effect of SAPS on soil and plant, can improve the soil characteristic like water holding capacity (WHC) so that soil can hold nutrient. Therefore, it can increase the nutrient uptake by plant and the good quality of yield can be achieved.